PERAN SASTRA ANAK DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI DI TPA AL WAHDA KUDUS - Sania Nailul Muna; Mila Roysa; Moh Kanzunnudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the role of children's literature in shaping the character of early childhood at TPA Al Wahda Kudus, as well as to analyze the effectiveness of the implemented Reading Program. This research uses a qualitative descriptive approach. Data were collected through observation, interviews with teachers, and documentation of children's developmental progress. The results showed that children's literature, integrated through the routine Reading Program, significantly contributed to the formation of positive characters, especially in overcoming psychological barriers such as shyness and adaptation difficulties. Children experienced a transformation into braver, more confident individuals and showed improvement in social-emotional aspects. The study concludes that the structured selection of children's literature stories acts as an effective medium for early childhood character internalization.